Enantiocomplementary Michael Additions of Acetaldehyde to Aliphatic Nitroalkenes Catalyzed by Proline‐Based Carboligases. (2nd February 2022) - Kunzendorf, Andreas; Saifuddin, Mohammad; Poelarends, Gerrit J.
Abstract: The blockbuster drug Pregabalin is widely prescribed for the treatment of painful diabetic neuropathy. Given the continuous epidemic growth of diabetes, the development of sustainable synthesis routes for Pregabalin and structurally related pharmaceutically active γ‐aminobutyric acid (GABA) derivatives is of high interest. Enantioenriched γ‐nitroaldehydes are versatile synthons for the production of GABA derivatives, which can be prepared through a Michael‐type addition of acetaldehyde to α, β‐unsaturated nitroalkenes. Here we report that tailored variants of the promiscuous enzyme 4‐oxalocrotonate tautomerase (4‐OT) can accept diverse aliphatic α, β‐unsaturated nitroalkenes as substrates for acetaldehyde addition. Highly enantioenriched aliphatic ( R )‐ and ( S )‐γ‐nitroaldehydes were obtained in good yields using two enantiocomplementary 4‐OT variants. Our results underscore the synthetic potential of 4‐OT for the preparation of structurally diverse synthons for bioactive analogues of Pregabalin. Abstract : Enantiocomplementary Michael additions : The application of two tailor‐made enantiocomplementary carboligases allow for the stereodivergent synthesis of aliphatic γ‐nitroaldehydes, which are useful precursors for pharmaceutically active analogues of the blockbuster drug, Pregabalin. Good isolated product yields and excellent enantiopurity (up to >99 : 1 e.r.) were achieved.